Religion AI And The Growth Of Online Gospel - Segun, Adediran Idowu; Adekoya, Samuel Olamide; Adegbite, Deborah Doyinsola (Corpus Intellectual, 2024)
This study explores the intersection of religion, artificial intelligence (AI), and the growth of the online gospel, focusing on the implications for contemporary faith practices. The rapid integration of AI into religious contexts has transformed how the gospel is disseminated, raising critical questions about the authenticity and communal aspects of spiritual experiences This research aims to critically explore the influence of AI on online gospel dissemination, focusing on the ethical and theological challenges that emerge from this digital shift. Utilising Media Ecology Theory, proposed by Marshall McLuhan, this study contextualises the impact of technology on religious practices. Employing a mixed-methods approach that combines theological, historical, and phenomenological research, the study offers a thorough understanding of how AI impacts religious experiences. It also explores the gaps in existing literature on how AI affects traditional religious practices and the personalisation of faith in digital environments. Findings reveal that while AI-driven applications enhance accessibility and personalisation, they also pose risks to doctrinal integrity and communal worship. Additionally, the reliance on digital platforms may dilute the authenticity of religious experiences. This research adds to academic discourse by offering a detailed analysis of the challenges and opportunities that AI and digital media bring to religious practice. Based on these findings, the study offers the following five recommendations to the religious organisation and other stakeholders in the AI:(I) Develop ethical guidelines for AI usage in religious contexts, (II) Enhance digital literacy programs for faith communities, (III) Foster hybrid worship models that integrate online and in-person experiences, (IV) Encourage collaborative content creation among congregants, and (V) Conduct ongoing research to monitor the evolving impacts of digital evangelism.